"I don't throw away food, unless I see that it's not fit for consumption": An in-depth exploration of household food waste in Uruguay. (January 2022) - Ferro, Camila; Ares, Gastón; Aschemann-Witzel, Jessica; Curutchet, María Rosa; Giménez, Ana
Graphical abstract: Highlights: Views on household food waste among Uruguayan citizens were explored via in-depth interviews. Drivers of food waste related to behavioral, personal, product and contextual factors were identified. Self-perception of household food waste was low among participants. Household food waste at country level was perceived as high among participants. Behavioral factors were the most frequently mentioned drivers of household food waste. Abstract: Significant reductions in household food waste have been regarded as a key step towards achieving global sustainable development. Household food waste is a complex phenomenon determined by consumer behavior along the steps of the "food journey" that goes from purchasing to final disposal. Although avoiding food waste is socially desirable and raises positive attitudes, consumers do not frequently engage in avoidance behaviors. The objectives of the present work were: i) to explore the views of Uruguayan citizens on household food waste, and ii) to identify drivers of food waste among Uruguayan households. A total of 20 in-depth interviews based on a semi-structured guide were conducted by telephone. Participants were asked to recall and describe the last time they discarded food, as well as to describe the most common food waste situations in their household, the most commonly used strategies to avoid food waste and how they could reduce it. The transcripts were analyzed using content analysis based on a deductive-inductive approach. Interviews revealed that most of the participants perceived food waste in their homes as null or low, whereas food waste in the country was regarded as high. When participants described food waste incidents, they perceived it as 'unavoidable', suggesting that they tended to find a rational explanation outside of their will to justify their behavior. Participants' discourses enabled the identification of drivers related to behavioral factors, personal factors, product factors, and contextual factors. Results stress that most promising entry points for communication campaigns and intervention programs to reduce household food waste should focus on behavioral factors, planning throughout all the household stages of the food journey and the provision of knowledge and skills on food storage, handling, and preparation.